Cooperation in Empty Container Logistics - Carlos Jahn; Johannes Schlingmeier (Innovative Methods in Logistics and Supply Chain Management: Current Issues and Emerging Practices. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 18, 2014)
Seaborne container transport volumes have doubled between 2001 and 2011 from 59 to 118 million TEU. The demand for container transport also induces demand for empty container repositionings, as not all import locations have an equally large demand for export of containerized cargo. As a result, empty containers have to be transported from equipment surplus- to deficit-locations. Around 25% of all transported containers are empty, resulting in costs of USD 33 billion in 2011. Since overcapacity in the industry has put margins under pressure and empty transports are often not paid for by the shipper, limiting those expenses is crucial for carriers. While technology-, pricing- and operations research-related approaches have been implemented widely, cooperative strategies have received little attention in practice. The literature attributes this to the fact that the benefits of such a strategy have not been proven yet. Based on the network-model, we believe, that an interchange of equipment between carriers in surplus- and deficit-locations will reduce the required number of empty moves. The paper constitutes the first empirical analysis of the potential of equipment interchange and will reveal that between 5-10% of moves can be avoided. The analysis is conducted as a case study and based on actual container moves collected from nine global container carriers. By proving t he benefits of equipment interchange, we hope to contribute to further cooperation among carriers.
10419/209188; https://econpapers.repec.org/RePEc:zbw:hiclpr:19
Keywords: 650; empty container logistics; cooperation; equipment interchange; imbalances